Eccentric Exercise in Patients with Chronic Health Conditions: A Systematic Review - Roig, Marc (University of Toronto Press Incorporated, 2008)
PURPOSE: The capacity of eccentric actions to produce muscle hypertrophy, strength gains, and neural adaptations without stressing the cardiopulmonary system has led to the prescription of eccentric training programmes in patients with low tolerance to exercise, such as elders or those with chronic health conditions. The purpose of this systematic review was to analyze the evidence regarding the effectiveness and suitability of eccentric training to restore musculoskeletal function in patients with chronic diseases. SUMMARY OF KEY POINTS: Relevant articles were identified from nine databases and from the reference lists of key articles. Articles were assessed to determine level of evidence and scientific rigour. Nine studies met the inclusion criteria. According to Sackett's levels of evidence, 7 studies were graded at level IIb, 1 study at level IV, and the remaining study at level V. Articles were also graded for scientific rigour according to the PEDro scale. One study was rated as high quality, 4 studies were rated as moderate, and 2 studies were graded as poor quality. CONCLUSIONS: Eccentric training may be safely used to restore musculoskeletal function in patients with some specific chronic conditions. However, the heterogeneity of diseases makes it very difficult to extrapolate results and to standardize clinical recommendations for adequate implementation of this type of exercise. More studies are needed to establish the potential advantages of eccentric training in chronic conditions.